2019
DOI: 10.1002/tkm2.1206
|View full text |Cite
|
Sign up to set email alerts
|

Ninjin'yoeito for symptoms of frailty: Successful treatment of three cases

Abstract: Cases Patient 1 was an 81‐year‐old patient with general fatigue. Patient 2 was a 56‐year‐old patient who felt cold, with general fatigue and dry cough, after operation for lung cancer; and patient 3 was a 55‐year‐old woman with interstitial pneumonia after breast cancer treatment, who reported feeling cold, with general fatigue and a tendency to catch colds. Outcome Patient 1’s cognition and dry skin were improved by changing hachimigan and hochuekkito to ninjin'yoeito; patients 2 and 3 were effectively treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Table 4 presents the list of clinical studies and Table 5 presents the list of case reports of NYT according to the search strategy. Five randomized clinical trials (RCT) [59][60][61][62][63], four observational studies [64][65][66][67], and 12 case reports were searched [68][69][70][71][72][73][74][75][76][77][78][79][80]. Herein, we summarize the findings of clinical studies on NYT.…”
Section: Clinical Results and Applications From Clinical Trials And C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 presents the list of clinical studies and Table 5 presents the list of case reports of NYT according to the search strategy. Five randomized clinical trials (RCT) [59][60][61][62][63], four observational studies [64][65][66][67], and 12 case reports were searched [68][69][70][71][72][73][74][75][76][77][78][79][80]. Herein, we summarize the findings of clinical studies on NYT.…”
Section: Clinical Results and Applications From Clinical Trials And C...mentioning
confidence: 99%
“…Morinaga et al reported a case with hip fracture and sarcopenia whose appetite loss, nutritional status, body weight, and muscle mass improved by NYT [71]. Kimura et al reported three cases whose general fatigue was improved by NYT [72]. Hirai et al also reported a case whose body weight, muscle mass, frailty score, COPD score, and anxiety and depression score were improved by NYT [73].…”
Section: Clinical Results and Applications From Clinical Trials And C...mentioning
confidence: 99%
“…Further, the hochuekkito group tended to have an increase in body weight and serum albumin levels compared with their respective values in the control group ( 13 ). Ninjinyoeito, which is another hozai for such as frailty ( 33 ), has also been used for NTM-PD. Nogami et al reported the efficacy of ninjinyoeito in a patient with NTM-PD due to Mycobacterium fortuitum , who did not improve despite receiving guideline-based therapy for 2 years ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, clinical studies on the use of ninjin'yoeito have demonstrated efficacy in patients with lung cancer ( 11 ), pulmonary non-tuberculous mycobacteriosis ( 14 ), pharyngeal vascular malformation ( 15 ), anemia associated with chronic hepatitis C ( 16 ), chronic inflammation and poor QOL due to hemodialysis ( 17 ), depression associated with Alzheimer-type dementia (when used in combination with donepezil) ( 18 ), and frailty ( 19 22 ). Rikkunshito is a formulation comprising eight crude drugs, five of which are also included in ninjin'yoeito: ginseng, Atractylodes rhizome, Poria sclerotium, C. unshiu peel, and Glycyrrhiza .…”
Section: Discussionmentioning
confidence: 99%